Chitosan: Microsphere Formulation and Characterization for Slow-Release Prebiotic Activities in Gut Microbiota Remodelling - Kumar, Sunny; Bhatia, Zeel; Seshadri, Sriram (Recent Advances in Drug Delivery and Formulation, 2025)
IntroductionChitosan is a biocompatible, mucoadhesive, and biodegradable polymer widely used for various purposes due to its biological activity and safety. The current study aimed to formulate Chitosan microspheres and conduct an in-vitro evaluation of their cytotoxicity. The concept is focused on targeted gut delivery and biological activities in gut microbiota remodelling.MethodsThe formulations were comprehensively characterized, encompassing SEM for surface morphology, particle size analysis, and FT-IR for structural understanding. Along with biological activity and cytotoxicity studies, dissolution efficiency was considered to understand release kinetics potential and accelerated stability studies to predict formulation shelf-life.ResultsThe formulation showed smooth spherical surface morphology with an average size range of 30.0 ± 5.0 µm and a charge of 20.35 ± 0.35 mV. Further, functional and thermal properties were determined using FT-IR and DSC, respectively. The microspheres showed a potent prebiotic potential in gut flora isolated and processed from a faecal sample of Wistar rats with prolonged release characteristics in the dissolution study. A cytotoxicity study using rat intestinal epithelial cells (IEC6) indicated that 40 mg /kg of microspheres could be considered an optimal dose for an in-vivo study.ConclusionThe formulation demonstrated promising pharmaceutical applicability due to its potential prebiotic nature and slow release into the gut environment. After a thorough in vivo study, the microspheres can be broadly used to restore gut dysbiosis due to their potential prebiotic activities in various diseases and disorders, including but not limited to obesity, type-2 diabetes, cardiometabolic disease, and non-alcoholic fatty liver disease.
Keywords: biodegradable polymer